A shift towards the annual habit in selfing Arabidopsis lyrata. (30th September 2020) - Gorman, Courtney E.; Steinecke, Christina; van Kleunen, Mark; Dorken, Marcel E.; Stift, Marc
Abstract : An annual life history is often associated with the ability to self-fertilize. However, it is unknown whether the evolution of selfing commonly precedes the evolution of annuality, or vice versa . Using a 2-year common garden experiment, we asked if the evolution of selfing in the normally perennial Arabidopsis lyrata was accompanied by a shift towards the annual habit. Despite their very recent divergence from obligately outcrossing populations, selfing plants exhibited a 39% decrease in over-winter survival after the first year compared with outcrossing plants. Our data ruled out the most obvious underlying mechanism: differences in reproductive investment in the first year did not explain differences in survival. We conclude that transitions to selfing in perennial A. lyrata may be accompanied by a shift towards annuality, but drivers of the process require further investigation.